An intervertebral disc whole organ culture system to investigate proinflammatory and degenerative disc disease condition. (6th February 2018) - Lang, Gernot; Liu, Yishan; Geries, Janna; Zhou, Zhiyu; Kubosch, David; Südkamp, Norbert; Richards, R. Geoff; Alini, Mauro; Grad, Sibylle; Li, Zhen
Abstract: The aim of this study was to compare the effect of different disease initiators of degenerative disc disease (DDD) within an intervertebral disc (IVD) organ culture system and to understand the interplay between inflammation and degeneration in the early stage of DDD. Bovine caudal IVDs were cultured within a bioreactor for up to 11 days. Control group was cultured under physiological loading (0.02–0.2 MPa; 0.2 Hz; 2 hr/day) and high glucose (4.5 g/L) medium. Detrimental loading (0.32–0.5 MPa, 5 Hz; 2 hr/day) and low glucose (2 g/L) medium were applied to mimic the condition of abnormal mechanical stress and limited nutrition supply. Tumour necrosis factor alpha (TNF‐α) was injected into the nucleus pulposus (100 ng per IVD) as a proinflammatory trigger. TNF‐α combined with detrimental loading and low glucose medium up‐regulated interleukin 1β (IL‐1β), IL‐6, and IL‐8 gene expression in disc tissue, nitric oxide, and IL‐8 release from IVD, which indicate a proinflammatory effect. The combined initiators up‐regulated matrix metalloproteinase 1 gene expression, down‐regulated gene expression of Type I collagen in annulus fibrosus and Type II collagen in nucleus pulposus, and reduced the cell viability. Furthermore, the combined initiators induced a degradative effect, as indicated by markedly higher glycosaminoglycan release into conditioned medium. The combination of detrimental dynamic loading, nutrient deficiency, and TNF‐α intradiscal injection can synergistically simulate the proinflammatory and degenerative disease condition within DDD. This model will be of high interest to screen therapeutic agents in further preclinical studies for early intervention and treatment of DDD.